Konstelasi Faktor Individual, Organisasional, dan Situasional dalam Pembentukan Perilaku Etis Akuntan - Sintia Nur Afifah; Habsyah Fitri Aryani (Economics and Business Faculty UNUSIA, 2026)
Accountants' ethical behavior is a fundamental aspect in maintaining the integrity of the profession and public trust in financial information. In professional practice, accounting decision making is not only influenced by technical competence, but also by moral considerations shaped by individual, organizational and situational factors. Various empirical studies have examined these factors, but the results are still fragmented and do not provide an integrated understanding. This research aims to systematically examine the factors that influence accountants' ethical behavior through a Systematic Literature Review (SLR) approach. Literature searches were carried out using Google Scholar and Publish or Perish, with the criteria being articles in accredited journals SINTA 4 and SINTA 5 for the period 2014–2024. A total of 12 selected articles were analyzed using a thematic synthesis approach. The research results show that accountants' ethical behavior is formed through complex interactions between individual, organizational and situational factors. Individual factors act as basic capacities in ethical judgment, organizational factors as controlling mechanisms through culture and value systems, and situational factors as triggers that test behavioral consistency under conditions of work pressure. Analysis shows that situational pressure has the strongest tendency to trigger unethical behavior, especially when it is not balanced by adequate organizational support.